AN ANALYSIS THE MORAL MESSAGE ON NARRATIVE TEXT FOUND IN TEXT BOOKS OF SMA KOSGORO - Sugiarti Sugiarti (State Institute for Islamic Studies IAIN of Metro, 2015)
Education is one of essential aspects for Indonesia when it wants to advance its national life through young generation. Young generation as the future of nation is a familiar words accepted by a large number of people in this country.The case of students’ morality commonly found in the school proves that to give moral message in all chances of lesson is important. The study used qualitative research to find the data. Reseacher analyzed 22 narrative text books. The result shows that narrative texts as kind of literature are frequently found in English text books of senior high school also narrative texts found in English text books of senior high school Kosgoro Sekampung are commonly found in the form of fable. Since, narrative text is favorable text in a major of students; the teachers hopefully are expected to employ it as the topic in making ice-breaking or brainstorming before start for teaching.